Glucocorticoid receptor-dependent disruption of a specific nucleosome on the mouse mammary tumor virus promoter is prevented by sodium butyrate. - Bresnick, E H (1990)
Our laboratory has previously developed cell lines derived from mouse NIH 3T3 fibroblasts and C127 mammary tumor cells that stably express mouse mammary tumor virus (MMTV) long terminal repeat fusion genes in bovine papillomavirus-based episomes. Glucocorticoid hormone strongly activates transcription from episomes and induces the disruption of a single nucleosome in an array of phased nucleosomes on the MMTV promoter. Sodium butyrate inhibits the glucocorticoid hormone-dependent development of a nuclease-hypersensitive site that is due to the displacement of this nucleosome, and inhibits induction of RNA transcripts from episomes. Saturation binding studies show that butyrate treatment does not significantly affect the amount or the hormone-binding affinity of the glucocorticoid receptor. In a transient transfection assay, glucocorticoid hormone can activate transcription from a MMTV long terminal repeat-driven luciferase gene construct equivalently in untreated and butyrate-treated cells, indicating that the soluble factors necessary for transactivation of the MMTV promoter are unaffected by butyrate. The differential effect of butyrate on the induction of stable chromatin templates and transiently expressed plasmids suggests that butyrate prevents nucleosome displacement and represses transcription by inducing a modification of chromatin.